Isolation of Flavonoid Compounds Derived from Buni Leaves (Antidesma bunius (L) Spreng.) - Tonel Barus; Ria Agnes Adelina Manalu; Lamek Marpaung (Journal of Chemical Natural Resources, 2024)
The flavonoid compounds from the leaves of buni (A. bunius (L) Spreng.) have been isolated through a process of maceration utilizing methanol as the solvent. The concentrated methanol extract was combined with ethyl acetate. The concentrated ethyl acetate extract was subsequently dissolved in methanol and subjected to partition extraction using n-hexane. The concentrated methanol extract was acidified with 6% HCl, followed by partition extraction using chloroform. The concentrated chloroform extract was isolated using column chromatography, employing an eluent mixture of n-hexane and ethyl acetate in the following ratios: 90:10, 80:20, 70:30, and 60:40 (v/v). The compounds underwent purification via TLC preparative, resulting in a tawny paste with a mass of 30 mg and an Rf value of 0.31. The compound underwent additional identification through the application of Ultraviolet Visible (UV-Vis) spectroscopy, Fourier Transform-Infrared Spectroscopy (FT-IR), and Proton Nuclear Magnetic Resonance Spectroscopy (1H-NMR), leading to the conclusion that the flavonoid in question is isoflavone.